Pseudoproleptus sp. Larvae (Nematoda: Cystidicolidae) parasitizing Macrobrachium amazonicum (Decapoda: Crustacea) in the state of Pará, Northern Brazil - Patrick José Colares Cardoso; Liane Rodrigues Galvão de Cristo; Yan Rafael Gillet Santa Brigida; Elane Guerreiro Giese; Raul Henrique da Silva Pinheiro (Revista Brasileira de Parasitologia Veterinária)
Abstract Third-stage larvae of a nematode species were found encapsulated in the cephalothorax of Macrobrachium amazonicum from the Guamá River, municipality of Belém, in the state of Pará, northern Brazil. Of a total of 120 specimens of M. amazonicum that were caught, 15.8% were parasitized with Cystidicolidae larvae that had morphological characteristics compatible with the genus Pseudoproleptus, such as rounded cephalic end, two pseudolips, slit-shaped buccal opening with four large submedian lips, vestibule with prostom and conical tail with a small mucron. The low presence of Pseudoproleptus larvae did not affect the growth of the shrimp, but these results cannot be generalized since the sampling was relatively low. Therefore, so the occurrence of this nematode could still negatively affect the growth and reproduction of these shrimp, leading to their death, which could directly affect their population dynamics and consumption by the Amazonian riverside population. Finally, we recommend more analyses with a greater sampling effort.